MACHINE LEARNING APPROACH FOR FAKE JOB AD PREDICTION - Putta. Srivani, Syeda Sufiya Rana, Dereddy Tejeswani, K. Noor E Afshan, Chukka Sathvika, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In modern time, the development in the field of industry and technology has opened a huge opportunity for new and diverse jobs for the job seekers. With the help of the advertisements of these job offers, job seekers find out their options depending on their time, qualification, experience, suitability etc. Recruitment process is now influenced by the power of internet and social media. Since the successful completion of a recruitment process is dependent on its advertisement, the impact of social media over this is tremendous. Social media and advertisements in electronic media have created newer and newer opportunity to share job details. Instead of this, rapid growth of opportunity to share job ads has increased the percentage of fraud job postings which causes harassment to the job seekers. So, people lack in showing interest to new job postings due to preserve security and consistency of their personal, academic and professional information. Thus, the true motive of valid job postings through social and electronic media faces an extremely hard challenge to attain people’s belief and reliability. Technologies are around us to make our life easy and developed but not to create unsecured environment for professional life. If jobs ads can be filtered properly predicting false job ads, this will be a great advancement for recruiting new employees.